Gambaran Kepatuhan Minum Obat Pasien Pprolanis di Puskesmas Wua-Wua - Haris, Restu Nur Hasanah; Masrida, Wa Ode; Ali, Nur Fitriana Muhammad; Fitriani, Rezky Dwi; Irwan, Irwan; Hayati, Siti (Jurnal Sains, Teknologi dan Kesehatan, 2024)
Prolanis is a proactive program that is integrated and developed directly by BPJS Health with the main objective of reducing the risk of complications. Every year the number of Prolanis patients in several health facilities in Kendari City is increasing. The purpose of treatment is not only for treatment, but also to prevent complications and improve the patient's quality of life. The existence of this prolanis will minimize this, the mortality rate of non-communicable diseases, especially hypertension and diabetes mellitus. The purpose of this study was to look at the description of drug compliance in prolanis patients at the Wua-wua Health Center. Cross-sectional research design, sampling technique using total sampling. The research instrument used the MMAS-8 instrument to measure the level of compliance in taking medication for prolanis patients. Materials and data sources in this study were taken from prolanis patients who were undergoing treatment at the Wua-wua Health Center. The results showed that prolanis patients at the Wua-wua Health Center were in the compliant category (5%), moderate (30%) and non-compliant (65%). The majority of prolanis patients at the Wua-wua Health Center are non-compliant. Patient non-adherence is caused by forgetting to take medicine, feeling that the condition is getting better, feeling uncomfortable with the medicine and it is still often difficult to remember to take medicine.